2017
DOI: 10.18203/2320-6012.ijrms20171241
|View full text |Cite
|
Sign up to set email alerts
|

Management of intra-articular fracture of distal femur with LCP and Lag screws in adults

Abstract: Background: Accurate reconstruction of articular surface of distal femur by closed manipulation is not possible. The recent trend for displaced intra-articular fractures of the distal femur is open reduction and stable osteosynthesis with early rehabilitation. The best exposure is achieved through Swashbuckler approach with good results. Purpose of the study was to review the surgical management with LCP and lag screws of complex and most challenging intra-articular fracture of distal femur.Methods: 30 cases o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 11 publications
6
15
0
Order By: Relevance
“…The nailing technique has disadvantages of lack of alignment control, intra-articular distribution of reaming debris and the intra-articular insertion [12] . Age incidence: In present study, the mean age was 41.4 years which is comparable to the observations of Daroch M S et al [21] . With mean of 45 years, Jillala S R et al [22] and Pascarella R et al [23] reported mean age as 51 and 62 years respectively.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The nailing technique has disadvantages of lack of alignment control, intra-articular distribution of reaming debris and the intra-articular insertion [12] . Age incidence: In present study, the mean age was 41.4 years which is comparable to the observations of Daroch M S et al [21] . With mean of 45 years, Jillala S R et al [22] and Pascarella R et al [23] reported mean age as 51 and 62 years respectively.…”
Section: Discussionsupporting
confidence: 90%
“…Gender predilection: In our study, males were 56 (93.3%) and females were 4 (6.7%). In the studies conducted by Jillala S R et al [22] , there were 31 (54.38 %) males and 26 (45.61 %) females, Daroch M S et al [21] reported as males are more commonly involved with 25 males (83.33%) as compare to females with 5 Cases (16.67%) because males are involved more in outdoor activities, Pascarella R et al [23] reported female predominance with 35 male and 54 female patients, Acharya K N et al [26] reported 20 male and 7 female patients among study population. The reason might be road traffic accident being the predominant cause of trauma.…”
Section: Discussionmentioning
confidence: 94%
“…Several other studies have also reported the outcome of LCP in the treatment of distal femoral intra-articular fractures [11][12][13][14][15][16]. It should be noted that the conflicting results of the different investigations are attributed to the different characteristics of the patients, such as age, fracture type, concurrent fractures, etc.…”
Section: Discussionmentioning
confidence: 99%
“…The AO principle in the operative treatment of intra-articular fractures involves anatomical reduction of the articular surface of the fracture, rigid fixation and early mobilization. The advent of Distal Femoral Locking Plate (DFLP) has promised excellent results in the management of these challenging fractures [11]. Direct exposure of the articular surface ensuresanatomic reduction, reduces time of surgery and subsequent lesser number of complications.…”
Section: Discussionmentioning
confidence: 99%